IL‐7 induces clathrin‐mediated endocytosis of CD127 and subsequent degradation by the proteasome in primary human CD8 T cells. Issue 2 (29th September 2015) - Faller, Elliott M; Ghazawi, Feras M; Cavar, Marko; MacPherson, Paul A
Abstract : Interleukin‐7 (IL‐7), a key immunoregulatory cytokine, plays an essential role in peripheral T‐cell homeostasis and function. Signaling via the IL‐7 receptor is tightly regulated and we and others have shown IL‐7 provides negative feedback on its own signaling by downregulating expression of the IL‐7 receptor alpha‐chain (CD127) through both suppression of CD127 gene transcription and by internalization of existing CD127 proteins from the cell membrane. We show here for the first time in primary human CD8 T cells that upon stimulation with IL‐7, CD127 is internalized through clathrin‐coated pits, a process dependent on both lipid‐raft formation and the activity of dynamin. As visualized by confocal microscopy, CD127 shows increased co‐localization with clathrin within 5 min of IL‐7 stimulation and within 15–30 min is seen in multiple intracellular punctae co‐localizing with the early endosomal marker EEA1. By 2 h after addition of IL‐7, CD127 staining associates with the late endosomal marker RAB7 and with the proteasomal 20S subunit. By inducing receptor internalization and translocation from early endosomes to the proteasome, IL‐7 directly influences its receptor density on the cell surface and thus regulates the intensity of its own signaling cascades. Given the important role IL‐7 plays in T‐cell development, homeostasis and function, deciphering how expression of its receptor is controlled on the cell surface is essential in understanding how T‐cell activity can be regulated in different microenvironments and in response to different pathogens.